The technique of the analysis of activity of insurance organizations - Kogut, O. U. (Journal of Economic Research & Business Administration, 2015)
The article considers method of analysis of the activities of insurance companies, , in particular: analysis of income formation of two types of insurance: compulsory insurance of civil liability of vehicle owners and voluntary property insurance of automobile transport.Expenses of the insurer formed in the distribution process of insurance fund. The composition and structure of expenditure is determined by two interrelated economic process: the satisfaction of liabilities to policyholders and fi nancing of the insurance company. In this regard, in the insurance business adopted the following classifi cation of expenses: expenses for insurance claims and insurance premiums, contributions to the reserve fund and reserve fees, charges to preventive measures; the costs of doing business. Together, these expenses represent cost of insurance operations. By specifi c weight and signifi cance in the socio-economic terms, the main item of expenditure of the insurer is paying insurance premiums and insurance reimbursement.